The effect of influencer credibility and brand experience on Conrad Bali hotel's Instagram brand image - Kadek Sri Utami; Nyoman Indah Kusuma Dewi; Muayyad Muayyad (Priviet Social Sciences Journal, 2026)
The disparity between the growth in Conrad Bali Hotel's Instagram following and the audience's perception of the brand serves as the driving force behind this study. The purpose of this study is to partially and concurrently examine how influencer credibility and brand experience affect the Conrad Bali Hotel's Instagram brand image. 110 active Conrad Bali Hotel Instagram followers who were exposed to marketing content on the platform were included in the quantitative analysis using a purposive sampling technique. Questionnaires were used to gather data, which were then analyzed using multiple linear regression, validity tests, reliability, classical assumptions, t-test, F-test, and coefficient of determination. With a computed t-value of 4.840 and a significance level of <0.001, the findings demonstrated that influencer credibility had a favorable and substantial impact on brand image. With a computed t-value of 5.236 and a significance of <0.001, brand experience also had a favorable and substantial impact on brand image. With a computed F-value of 137.898 and a significance of <0.001, both factors simultaneously had a favorable and substantial impact on brand image. According to the R Square value of 0.720, influencer credibility and brand experience account for 72% of the variation in brand image. This finding confirms that credible influencers and engaging brand experiences through Instagram can strengthen the brand image of Conrad Bali Hotel. Thus, Conrad Bali Hotel is advised to continue optimizing the use of influencers and engaging and authentic Instagram content to strengthen its brand image amidst the competitive hospitality industry.